Is Fitbit Charge 2 a feasible instrument to monitor daily physical activity and handbike training in persons with spinal cord injury? A pilot study - Maijers, M. C.; Verschuren, O.; Stolwijk-Swüste, J. M.; van Koppenhagen, C. F.; de Groot, S.; Post, M. W. M. (Spinal Cord, 2020)
Study design: It is a longitudinal pilot study. Objectives: To investigate the feasibility of a low-cost and widely used fitness tracker with step count and heart rate data to monitor daily physical activity in wheelchair users with spinal cord injury (SCI). Setting: Dutch community. Methods: Six participants with SCI who were in training for a handbike event were recruited. They were asked to wear a Fitbit Charge 2® 24 h a day for at least 2 weeks and were questioned about the utility and user-friendliness of this device. Results: Five out of six participants managed to wear the device nonstop for 2 weeks, and continued to wear the device after this initial period. Most participants were enthusiastic about the direct feedback provided by the tracker and reported the data to be accurate. Data collected during more than 2 months of three participants and during 8 months on one of them showed the possibility of detecting training days and observing interpersonal and intrapersonal variation in daily physical activity level. Conclusions: A commercially available, low-cost, self-monitoring multi-sensor wrist device or a fitness tracker like the Fitbit Charge 2® can be a promising instrument to monitor daily activity levels among wheelchair users with SCI. The free commercial dashboard and log data clearly show trends of variations in physical activity and increases in heart rate, which are of value to both researchers and clinicians interested in identifying training schedules of wheelchair athletes.